Teleconsultation for preoperative evaluation during the coronavirus disease 2019 pandemic: A technical and medical feasibility study. Issue 12 (December 2021) - Wienhold, Jan; Mösch, Lucas; Rossaint, Rolf; Kemper, Ilka; Derwall, Matthias; Czaplik, Michael; Follmann, Andreas
Abstract : BACKGROUND: During the surge in coronavirus disease 2019 (COVID-19) infections in early 2020, many medical organisations began developing strategies for implementing teleconsultation to maintain medical services during lockdown and to limit physical contact. Therefore, we developed a teleconsultation preoperative evaluation platform to replace on-site preoperative meetings. OBJECTIVE: This study assessed the feasibility of a teleconsultation for preoperative evaluation and procedure-associated adverse events. DESIGN: Implementation study. SETTING: A tertiary care university hospital in Germany from April 2020 to October 2020. PATIENTS: One hundred and eleven patients scheduled for elective surgery. INTERVENTION: Patients were assigned to receive teleconsultation for preoperative evaluation and to complete a subsequent survey. MAIN OUTCOME MEASURES: Primary endpoints were medical and technical feasibility, user satisfaction and time savings. RESULTS: For 100 out of 111 patients, telepreoperative consultations allowed for adequate perioperative risk assessment, patient education and also for effective collection of legal signatures. For six patients (5.4%), consultations could not be started because of technical issues, whereas for five patients (4.8%), clearance for surgery could not be granted because of medical reasons. A clear majority of anaesthetists (93.7%) rated the telepreoperative evaluations as equivalent to on-site meetings. The majority of the patients considered teleconsultation for preoperative evaluation as convenient as an on-site meeting (98.2%) and would choose a teleconsultation again (97.9%). Median travel time saved by patients was 60 min (Q1 40, Q3 80). We registered one adverse event: we detected atrial fibrillation in one patient only immediately prior to surgery. CONCLUSION: Telepreoperative evaluations are medically and technically feasible, yielding high satisfaction rates on both sides. However, regarding patient safety, not every patient is equally well suited. Overall, implementation of teleconsultation for preoperative evaluation into clinical routine could help maintain medical care during the COVID-19 pandemic. TRIAL REGISTRATION: NCT04518514, ClinicalTrials.gov Abstract : Supplemental Digital Content is available in the text